The Relationship Between the Ability to Think Positively and Academic Stress in Students Who Are Working on Thesis at Bina Darma University - Kartika Kartika; Sawi Sujarwo (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Academic stress is a common problem that is usually experienced by students. The source of the problems experienced by students is academic problems. One way to reduce academic stress is by thinking positively. In this research, quantitative methods were used with simple regression analysis, the population in this research was 2828 with a sample of 280 students. Analysis of the data used in this research is by using validity and reliability tests, assumption tests, statistical tests. Based on the research results, it can be concluded that there is a significant influence between the ability to think positively on the academic stress of Bina Darma University students in Palembang who are working on their thesis. Regression analysis results Simple results show that every one unit increase in positive thinking ability will reduce the level of academic stress by 0.67 units. In addition, the R-squared value of 0.45 indicates that 45% of the variability in academic stress can be explained by positive thinking skills. Validity and reliability tests also show that the instruments used, both to measure academic stress and positive thinking ability, have high validity and reliability, with Cronbach's Alpha values of 0.89 for academic stress and 0.87 for positive thinking ability respectively.